Redescription of Eudistoma magalhaensis (Michaelsen, 1907) (Ascidiacea) from Guaitecas Islands, Chile - Sanamyan, Karen; Schories, Dirk (Zootaxa, 2007)
The type species of the genus Paessleria Michaelsen 1907, known previously only from the original description is newly recorded from the Guaitecas Islands. All features of this species are characteristic of the genus Eudistoma confirming that Paessleria and Eudistoma are synonyms.